Organizational Commitment among Workers in Brewery Industry: Does Organizational Climate and Emotional Intelligence Counts? - Olabode D. Ibini; Blessing N. Ndu; Phebean E. Adelakun; Emmanuel E. Uye (Universitas Pahlawan Tuanku Tambusai, 2025)
The level of commitment to their organizations has been used as a parameter to determine the productivity of such organizations. Studies have used different predictors to determine organizational commitment with varied results. This study was conducted to examine the predictive ability of organizational climate and emotional intelligence on organizational commitment among workers in a brewery company. Cross-sectional survey design was employed while purposive sampling technique was used to select the study population. Data were conveniently collected from 250 participants using validated scales and analyzed using hierarchical multiple regression to test an hypothesis which was accepted at p <.001 level of significance. The results revealed that organizational climate and emotional intelligence jointly predicted organizational commitment among study participants [R2 =.051, F(2, 248) = 6.667, p <.001]. In addition, organizational climate (β =.128, p =.004) and emotional intelligence (β = -.186, p =.003) independently predicted organizat ional commitment among study participants. The study concludes that organizational climate and emotional intelligence are robust predictors of organizational commitment. Therefore, human resources managers should provide necessary welfare packages to improve workers’ organizational commitment.